An Assessment of the Impact of Government Policies on Broiler Production in Peninsular Malaysia - Benalywa, Zineb Abdulaker; Ismail, Mohd Mansor; Shamsudin, Mad Nasir; Yusop , Zulkornain (International Journal of Poultry Science, 2018)
Objectives: This study was designed to assess the impact of Malaysian government policies on broiler production in Peninsular Malaysia. Methodology: The study compared contract and non-contract farmers who produced and sold chickens according to three different production sizes. A policy analysis matrix containing policy protection indicators was used to evaluate the impact of government protection on broiler production in Peninsular Malaysia. Data were collected from 310 farms in Peninsular Malaysia using a field survey. Results: The results suggest that broiler production under contract farming is more profitable than under non-contract farming. Calculation of the nominal protection coefficient reveals that producers are not protected by the existing policies. Conclusion: The broiler industry is in need of government assistance in order to enhance its competitiveness.